PSYCHOSOCIAL AND PSYCHOPATHOLOGICAL CHARACTERISTICS OF SPANISH ADOLESCENTS SAMPLE THROW YOUTH SELF-REPORT/11-18. - Zubeidat, Ihab; Fernández-Parra, Antonio; Ortega, José Mª; Vallejo, Miguel Ángel; Sierra, Juan Carlos (Anales de Psicología / Annals of Psychology, 2009)
In this study we analyzed the psychosocial competences and psychopathological characteristics assessed by the YSR/11-18 in a sample of 961 Spanish adolescents from 13-18 years. The results indicated that men scored high in various social activities and externalized psychopa-thologies, while women have high scores for performance in different tasks and internalized symptoms. Younger adolescents showed higher scores than older ones in participation in groups and organizations, as well as in most of the YSR/11-18 syndromic scales, while older adolescent’s preferred no sports activities and works or tasks. Students at Compulsory Secondary Education and Non-Compulsory Secondary Education showed more activity than those in Vocational Training Cycles in all psychosocial competencies, but the latter overcame the first in most of the syndromic scales. Adolescents without romantic relation scored higher in the psycho-social competencies than those who enjoyed romantic relation, although the second ones showed more psychopathology than the first ones. Fi-nally, working (in addition to studying) did not seem to be relevant in determining differences regarding the psychosocial competencies and syndromic scales.